颈动脉蹼致反复卒中1例的诊疗体会及文献复习(Diagnosis and Treatment Experience of Recurrent Stroke Caused by Carotid Web: A Case Report and Literature Review) - 郭志慧，王小洁，汪利，姜斌，康晨瑶(GUO Zhihui, WANG Xiaojie, WANG Li, JIANG Bin, KANG Chenyao ) (Zhongguo cuzhong zazhi)
颈动脉蹼是一种临床相对少见的血管结构异常，作为隐源性卒中的重要病因之一，近年来逐渐受到临床关注。目前，国际指南尚未就该疾病的诊疗方案达成明确共识。本文报道了1例右侧颈内动脉系统卒中的患者，该患者经CTA及超声检查发现右侧颈动脉蹼，首次卒中后未行手术干预，随后出现卒中复发。本文结合诊疗过程及相关文献复习，分析颈动脉蹼致卒中的发病机制并总结诊疗体会。Abstract: Carotid web is a relatively rare vascular structural abnormality in clinical practice. As one of the important causes of cryptogenic stroke, it has gradually attracted clinical attention in recent years. Currently, international guidelines have not reached a clear consensus on the diagnosis and treatment of this disease. This paper reports a patient with right internal carotid artery system stroke. The patient was diagnosed with right carotid web through CTA and ultrasonography and did not undergo surgical intervention after the first stroke, subsequently experiencing a stroke recurrence. By combining the diagnosis and treatment process and reviewing relevant literature, this paper analyzes the pathogenesis of stroke caused by carotid web, and summarizes diagnosis and treatment experiences.